(untitled) (Journal of Economic Research & Business Administration, 2015)
The formulation of the strategic plan is held upon forecast prospects for the development of the firm, under certain assumptions about the changes in the external environment in which it operates. In general, strategic planning aims on adapting the firm to constantly change up the environmental conditions and to the benefits from the new features. This plan cannot, however, give a full and detailed picture of the future, but rather it provides a predictive scenario description of a probabilistic nature. Since strategic planning is associated primarily with the industrial organizations, it singles out the various levels of management: the enterprise in general (corporate); common areas of industrial and economic activities (departmental); specific activities (individual businesses); individual products. The paper proposes a strategic plan for the integrated development of industrial enterprise.